Anti-virus kit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Plant Viruses, Unique and Intriguing Pathogens Textbook of Plant Virology By L Bos, Backhuys Publishers, Leiden. 1999. 358 pp. ISBN 90 5782 012 9 NLG 150 Euro 68.05